Fabrication of ferroelectric bismuth titanate glass-ceramic by incorporation method - Pengpat K. (2014)
In this work the fabrication of glass-ceramics containing ferroelectric BIT crystals was carried out by incorporation method. The BIT powder was prepared by conventional ceramic method with calcination temperature of 800°C. In order to prepare bismuth titanate glass ceramic by incorporation method, the BIT powder was mixed with 25-95 mol% B2O3 as a glass former. The batches were melted in an air atmosphere using an electric furnace, at 1150°C for 15 minutes. After that, the melts were quenched between the stainless steel plates at room temperature. It was found that crystallization of unexpected Bi2Ti4O11 phase occurred in most of the glass - ceramics with the amount of B2O3 less than 70 mol%. This may cause from the evaporation of Bi2O3 during melting. Besides, glass could only be obtained from the melt of 80 mol% B 2O3 batch. In this glass, however, the small amount of TiC2 crystals was detected using SEM technique. The glasses with the amount of B2O3 more than 80% shows severe phase separation and crystallization of TiO2 and B2O3. The glasses of 80 mol% B2O3 composition were subjected to heat - treatment processes at 300 to 500°C. It was found that the crystallization of Bi2Ti4O11 phase occurred at 500°C while at 300°C and 400°C the glasses were still amorphous. The maximum dielectric constant (εr) of the heat treated glass ceramics was found in the range of 22-30. © 2008 Trans Tech Publications, Switzerland.